EKSPLORASI ETNOMATEMATIKA PEKERJA BANGUNAN DALAM MEMBANGUN RUMAH ETNIS MELAYU KETAPANG - Iqbal, Muhammad; Hamdani, Hamdani; Rustam, Rustam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the ethnomathematics of construction workers in building Ketapang Malay ethnic house. Research method used is descriptive with  case study approach. Subjects of this study were 4 workers with a skilled background in building house and thick culture with object of culture building workers' mathematics. The results is building revealed the terms Depa, Seta, Jar, Ukor, and Koyam as well as successive plots to measure the length of the land, the length of the connecting beams, round wood, the width of the room and the volume of the pond and the size of the working area. There are 4 terms of glegar, namely glegar, glegur, pillow, corpse. So that a series of numbers can be arranged from the number of rafter, namely 5,9,13,17,21,25 ..etc. Other findings on the building of the house that is the roof there is a roof of the sledge of two rectangular fields then the roof of the wire from two trapezoidal fields and two triangular fields. Stair house with ladder term, wait, and stay on the steps. The calculation can be arranged in a series of numbers from the number of steps that are 4, 7, 10, 13, 16 ... etc. Some parts of the house have a variety of decorations ranging from stairs, fences, ventillation, and windows that are rich in meaning where the making uses geometry and transformation  Keywords :           Exploration, Ethnomathematics, Ketapang Malay Ethnic House